Hyperfine interaction studies using low temperature nuclear orientation - Johnston, P; Johnston, P. D. (1972)
﻿ Experiments are described in this thesis using the techniques of nuclear orientation and nuclear magnetic resonance to study the hyperfine interactions of dilute impurities in ferromagnetic metal hosts. The work is particularly concerned with the study of systems for which the more accurate measurement of the hyperfine interaction by the observation of nuclear magnetic resonance provides more information about the hyperfine interaction, and the nuclear parameters of the radioactive impurity, than can be obtained by a nuclear orientation experiment alone. The two aspects of this theme are combined in several experiments, where an accurate description of the decay transitions depends on the ability to provide a complete description of the orientation of the parent nucleus, from the resonance experiment. The experimental results can be considered in two parts. The use of the nuclear resonance technique to study the hyperfine interactions of dilute impurities, has concentrated on the observation and measurement of contributions to the hyperfine interaction from localised orbital magnetic moments on heavy impurities in the three cubic ferromagnetic lattices, iron, cobalt and nickel. The mechanism of the formation of localised magnetic moments at impurity atoms is discussed in chapter four. The cubic symmetry of the three host lattices will tend to quench the orbital angular momentum of a substitutional ion, but the strong spin-orbit interaction associated with heavy impurities will compete with the crystal field, and tend to produce a small orbital magnetic moment localised at the impurity site. Such an effect can be observed through the detection and measurement of either the magnetic orbital dipolar hyperfine interaction or an electric quadrupole interaction. The nuclear resonance technique is sensitive to both these interactions in the appropriate circumstances. The two impurities studied have provided an example of each measurement. Two isotopes of gold, dissolved as dilute impurities in iron, cobalt and nickel, have enabled the magnetic orbital dipolar hyperfine fields to be studied through the measurement of the hyperfine anomaly. The comparison of the measured value of the hyperfine anomaly in these hosts with the known value associated with a pure S-electron contact hyperfine field, allows the contribution to the hyperfine fields from a non-contact, orbital field, to be separated and measured. Since both a magnetic orbital dipolar field and an electric quadrupole interaction will arise from the unquenching of the orbital angular momentum, the effect of both contributions on the ratio of the observed nuclear resonance frequencies of 198Au and 199Au must be measured. The table below shows the measured values for the hyperfine fields on these two isotopes Table 1 Isotope Host HTotal HContact HOrbital dipolar 198Au Fe andminus;1169(1) andminus;1389(30) +220(30) Co andminus;732(1) andminus;792(30) +60(30) Ni andminus;365.2(8) andnbsp; 199Au Fe andminus;1233(1) andminus;1453(30) +220(30) Co andminus;769(1) andminus;829(30) +60(30) Ni The other systems studied have been dilute impurities of iridium in nickel and cobalt. The interaction of the host conduction electrons of a nickel lattice with an iridium impurity his been shown by Demangent and Gantier [64] to result in the formation of a localised magnetic moment on the impurity. This has been detected in the N.M.R/O.N. experiments by the finite electric quadrupole interaction resulting from the unquenching of the orbital angular momentum, through the spin-orbit interaction. The comparison with other measurements, and with the estimate of the orbital dipolar hyperfine field, from the Mossbaiier measurements of the hyperfine anomaly between the ground and first excited states of 193Ir, have suggested a magnitude for the orbital magnetic moment of +0.2andmu;B. The second aspect of this study has used the knowledge of the hyperfine interaction from a nuclear resonance experiment to analyse nuclear orientation measurements on two isotopes, 110Agm and 192Ir, in terms of the M1/E2 mixing ratios of several of the gamma-ray transitions in the decay. Both of the decay products of these isotopes fall into mass regions where the excited states can be represented, to first order, by collective vibrational harmonic oscillations about a spherical equilibrium nuclear shape. Measurements of M1 admixtures, into the pure E2 transitions predicted on the basis of a perfect harmonic oscillator model, are of value in comparison with theories including a pairing-plus-quadrupole force [54]. The results from the nuclear orientation experiments are compared with similar measurements by the gamma-gamma correlation technique, and are found to be in general agreement, with frequently a much improved accuracy. The results, particularly for 110Cd suggest large perturbations of simple harmonic oscillator excitations. Previous nuclear orientation experiments on these isotopes hare suffered from an inaccurate, and often very wrong, value for the hyperfine interaction, due to a non-unique distribution of hyperfine fields in the alloys used. The comparison with the nuclear magnetic resonance experiments has enabled good alloys, with impurity concentrations less than 10andminus;3 at %, to be used, and the distribution of hyperfine fields in more concentrated, and non-substitutional alloys to be studied. The theoretical basis of the nuclear orientation, and the observation of nuclear magnetic resonance by the perturbation of the thermal equilibrium gamma-ray anisotropic distribution from a system of oriented nuclei, is discussed in chapter one. The cryogenic apparatus and the experimental procedure is discussed in chapter two, including nuclear magnetic resonance measurements on three simple systems Fe 60Co, Co 60Co, and Fe 96To. Nuclear magnetic resonance studies on impurities of silver, gold, and iridium are presented in chapters three, six and seven.